Effect of Non-Newtonian Fluid Behavior on Forced Convection from a Cluster of Four Circular Cylinders in a Duct, Part I: Power-Law Fluids. Issue 1 (21st December 2021) - Trivedi, Mohit; Nirmalkar, Neelkanth; Gupta, Anoop K.; Chhabra, Rajendra P.
Abstract: Forced convection heat transfer in power-law fluids has been investigated numerically around four identical circular cylinders in a diamond array in a square enclosure. For the laminar flow, the governing equations have been solved numerically over the following ranges of parameters: Reynolds number (5 − 200), Prandtl number (0.7 − 100), power-law index (0.2 − 2) and center-to center gap between cylinders (0.3 − 0.7) to elucidate their influence. The detailed kinematics and engineering parameters are influenced by the gap between the cylinders via the development of multiple secondary flow regions and/or the splitting of incoming fluid stream. The drag on the trailing cylinders with reference to the lead cylinder can be up to ± ∼ 80% higher or lower depending upon the gap between the cylinders, power-law index and Reynolds numbers. In compact arrays, the drag becomes slightly negative due to the reverse flow for certain combinations of power-law index (< 1) and high Reynolds numbers (100 and 200). Similarly, the heat transfer affected by the subsequent cylinders ranges from 50-60% for the second cylinder which drops to ∼10% for the last cylinder. Finally, the functional dependence of the Nusselt number has been consolidated in terms of Reynolds number, Prandtl number, power-law index and the gap ratio.